Judicial Reform Index for Armenia - (:unkn) unknown (My University, 2016)
The Judicial Reform Index (JRI) is a tool developed by the American Bar Association’s Centraland East European Law Initiative (ABA/CEELI). Its purpose is to assess a cross-section offactors important to judicial reform in emerging democracies. In an era when legal and judicialreform efforts are receiving more attention than in the past, the JRI is an appropriate andimportant assessment mechanism. The JRI will enable ABA/CEELI, its funders, and the emergingdemocracies themselves, to better target judicial reform programs and monitor progress towardsestablishing accountable, effective, independent judiciaries.